Factors Affecting the Module Completion of Grade 12 Students: Basis for Intervention Program and Policy Development - Sumandal, Allan (Future Science / FSH-PH Publications, 2022)
This study investigated the contributing factors that affect the module completion of Grade 12 students in Governor Alfredo M. Abueg Sr. National Technology and Vocational Memorial High School, Brooke’s Point, Palawan. A descriptive-correlation method was utilized as the research design of this study. A validated researcher-made questionnaire written in English which was based on a 5-point Likert Scale was distributed to a sample of 46 regular Grade 12 students. Respondents were randomly selected from seven (7) different Technical-Vocational Livelihood (TVL) courses. Findings revealed that most of the respondents belong to the age bracket of 17 or below, female, were living within the town and were with closely approximating proficiency in their General Weighted Average (GWA). Students rated “sometimes” that their module completion was affected by the factors such as the content of the Self-Learning Module, parental support, internet connection, social media, health condition, and proximity of the house from the school. The result of the regression analysis has shown that there was a weak association between teacher support and location as well as between internet connection and GWA of the student. Furthermore, the intervention measure was designed by the researcher. The findings of this study provided inputs to school heads and teachers to formulate intervention programs and policy development on the factors affecting students’ module completion.